Investigating the Influence of Intergroup Contact in Virtual Reality on Empathy: An Exploratory Study Using AltspaceVR - Tassinari, Matilde; Aulbach, Matthias Burkard; Jasinskaja-Lahti, Inga (Frontiers in Psychology, 2022)
Virtual Reality (VR) has often been referred to as an “empathy machine”. This is mostly because it can induce empathy through embodiment experiences in outgroup membership. However, the potential of intergroup contact with an outgroup avatar in VR to increase empathy is less studied. Even though intergroup contact literature suggests that less threatening and more prosocial emotions are the key to understanding why intergroup contact is a powerful mean to decrease prejudice, few studies have investigated the effect of intergroup contact on empathy in VR. In this study, we developed a between-participants design to investigate how VR can be used to create a positive intergroup contact with a member of a stigmatized outgroup (ethnic minority) and present the results of the effect of intergroup contact in VR on empathy. 64 participants experienced either positive contact (i.e. equal intergroup status, collaborative) with a black (experimenter-controlled) avatar (experimental condition) or no intergroup contact (i.e., ingroup contact with a white avatar; control condition), with situational empathy (personal distress and empathic interest) being measured through a self-report questionnaire up to a week before and right after the VR contact experience. The experiment showed that satisfying degrees of body ownership of participants’ own avatar and co-presence with the contacted avatar can be achieved in simple and universally accessible virtual environments such as AltSpace VR. The results indicated that while VR intergroup contact had no significant direct effect on empathy, exploratory analyses indicated that post-intervention empathic interest increased with stronger feelings of co-presence in the intergroup contact condition.